Series de Fourier en la planeación y optimización de trayectorias de vehículos acuáticos autónomos - Flabio Dario Mirelez Delgado; Elena Elsa Bricio Barrios; Santiago Arceo Díaz (Mundo Fesc)
The constant breeding of tilapia in ponds has emerged as a permanent source of income in rural areas, given the constant demand for this product. This work addresses the application of Fourier series and classical control in aquaculture, focusing on the integration of Fourier series for the parameterization of Cartesian trajectories that guide an autonomous vehicle. The vehicle's purpose is to feed tilapia specimens ( Oreochromis Niloticus ) in an aquaculture tank. The objective is to minimize the cost of building autonomous vehicle prototypes, ensuring safety by calculating and correcting speed and acceleration so that the prototype follows a predefined distribution route, favoring the growth of the specimens. This is achieved through a control law based on a mathematical model. The use of parameterized Fourier series allows efficient calculation of the vehicle's speed and acceleration, reducing the dependence on expensive sensors, without compromising the safety of the autonomous vehicle.